Comparison of Damping Effects of Two Types of Graphite Cast Iron - Kováčiková, Petra; Dubec, Andrej; Vavro, Ján (Manufacturing Technology Journal, 2019)
This paper deals with the evaluation of the graphite cast iron structure and change of the dynamic behavior dependent on the graphite shape. Structural analysis is focused on the study of cast iron with flake and globular graphite. These two materials have a considerable application in manufacturing due to its specific mechanical and physical properties. The production of gray cast iron is less demanding in terms of the technological process and the quality of the raw materials compared to ductile cast iron but this material is the best for the production of castings. Compared with cast steels are these graphite castings less susceptible to the notch effects of fatigue stress and have a higher value of damping. Internal damping occurs in the structure of the material and can be caused by its imperfection. Computational measurement of eigenshapes and eigenfrequencies was performed using modal analysis in the SolidWorks software environment.
Keywords: ductile cast iron; gray iron; flake graphite; finite element method